Implementation of the Internet of Things (IoT) in the Sustainable Agricultural Products Sales System - Soelistianto, Farida Arinie (Westscience Press, 2025)
The rapid development of the Internet of Things (IoT) has created new opportunities for transforming agricultural systems toward sustainability, particularly in agricultural product sales systems. This study aims to explore the implementation of IoT in sustainable agricultural product sales systems in Indonesia and to understand its economic, environmental, and social implications. Using a qualitative research approach, data were collected through in-depth interviews with five key informants representing farmers, agribusiness actors, technology providers, and supporting institutions involved in IoT-based agricultural practices. The findings reveal that IoT implementation supports real-time monitoring of product quality, inventory management, traceability, and sales coordination, which contribute to improved market transparency and efficiency. Economically, IoT helps reduce post-harvest losses, strengthens bargaining positions, and stabilizes income. Environmentally, it supports waste reduction and promotes environmentally responsible sales practices. Socially, IoT enhances trust and collaboration among stakeholders, although challenges related to digital literacy, infrastructure limitations, and investment costs remain significant. Overall, this study demonstrates that IoT has strong potential to support sustainable agricultural product sales systems in Indonesia, provided that its implementation is accompanied by institutional support, capacity building, and inclusive governance mechanisms.